Faktor-faktor yang Mempengaruhi Kecurangan Akuntansi (Studi Kasus pada PT. Bank Tabungan Negara (Persero) Tbk KC Medan) - Ahmad Aidil Siregar; Reza Hanafi Lubis (Politeknik Negeri Jakarta, 2022)
This research was conducted at PT. Bank Tabungan Negara (Persero) Tbk KC Medan which aims to test and analyze the factors that influence accounting fraud which consists of internal control, individual morality, motivation and obedience to accounting rules. This study uses a quantitative method with a questionnaire instrument. The population in this study were all employees at PT. Bank Tabungan Negara (Persero) Tbk KC Medan, amounting to 85 people. The number of samples selected by purposive sampling method was 37 people. The analytical method used is multiple linear regression analysis. The results showed that internal control, individual morality and motivation partially had a positive and significant effect on accounting fraud, and the obedience of accounting rules partially had a negative and significant effect on accounting fraud at PT. Bank Tabungan Negara (Persero) Tbk KC Medan. Meanwhile, simultaneously internal control, individual morality, motivation and compliance with accounting rules have a positive and significant effect on accounting fraud at PT. Bank Tabungan Negara (Persero) Tbk KC Medan.